Andhradēśa caritrasaṅgrahamu : Kri. Śa. 1857 varaku - Sōmaśēkharaśarma, Mallampalli, 1891-1963 (SAMP early 20th-century Indian books project, 1948)
Collective biographies of prominent personalities from Andhra Pradesh; covers until 1857.